Anti-neuroinflammatory effect of hydroxytyrosol: a potential strategy for anti-depressant development - Li, Shuaiguang; Shao, Huarong; Sun, Ting; Guo, Xinyan; Zhang, Xiaoyuan; Zeng, Qingkai; Fang, Shaoying; Liu, Xiaoyu; Wang, Fan; Liu, Fei; Ling, Peixue (Frontiers in Pharmacology, 2024)
Introduction: Depression is a complex psychiatric disorder with substantial societal impact. While current antidepressants offer moderate efficacy, their adverse effects and limited understanding of depression’s pathophysiology hinder the development of more effective treatments. Amidst this complexity, the role of neuroinflammation, a recognized but poorly understood associate of depression, has gained increasing attention. This study investigates hydroxytyrosol (HT), an olive-derived phenolic antioxidant, for its antidepressant and anti-neuroinflammatory properties based on mitochondrial protection. Methods:In vitro studies on neuronal injury models, the protective effect of HT on mitochondrial ultrastructure from inflammatory damage was investigated in combination with high-resolution imaging of mitochondrial substructures. In animal models, depressive-like behaviors of chronic restraint stress (CRS) mice and chronic unpredictable mild stress (CUMS) rats were examined to investigate the alleviating effects of HT. Targeted metabolomics and RNA-Seq in CUMS rats were used to analyze the potential antidepressant pathways of HT. Results: HT protected mitochondrial ultrastructure from inflammatory damage, thus exerting neuroprotective effects in neuronal injury models. Moreover, HT reduced depressive-like behaviors in mice and rats exposed to CRS and CUMS, respectively. HT’s influence in the CRS model included alleviating hippocampal neuronal damage and modulating cytokine production, mitochondrial dysfunction, and brain-derived neurotrophic factor (BDNF) signaling. Targeted metabolomics in CUMS rats revealed HT’s effect on neurotransmitter levels and tryptophan-kynurenine metabolism. RNA-Seq data underscored HT’s antidepressant mechanism through the BDNF/TrkB signaling pathways, key in nerve fiber functions, myelin formation, microglial differentiation, and neural regeneration. Discussion: The findings underscore HT’s potential as an anti-neuroinflammatory treatment for depression, shedding light on its antidepressant effects and its relevance in nutritional psychiatry. Further investigations are warranted to comprehensively delineate its mechanisms and optimize its clinical application in depression treatment.